Effectiveness of Bamboo Leaf Silica Applied with Nanosprayer and Growing Media on Yield of Red Beetroot (Beta vurgaris L.) - Hamawi, Mahmudah; Etica, Use; Maulana, Ilham Insan (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Silica protects plants from abiotic stress. Planting media provides a place to grow and nutrition for plant growth. The research aims to study the effect of bamboo leaf silica dosage and growing media on the yield of red beets cultivated in the lowlands. The research was designed using a completely randomized factorial design (CRD) with two treatment factors. The first factor is the dose of bamboo leaf silica fertilizer (0 ppm, 0.15 ppm, 0.30 ppm, 0.45 ppm, 0.60 ppm). The second factor is the growing media (soil growing media; soil growing media + goat manure, and soil growing media + goat manure + husk charcoal). Research results: bamboo leaf silica dosage (0.3 ppm, 0.45 ppm and 0.60 ppm) affects the chlorophyll b and total chlorophyll. Growing media soil + goat manure + husk charcoal affects the length of red beet plants, number of leaves, diameter and length of red beetroots, wet weight and dry weight of red beetroots. Combination of growing media treatment (soil + goat manure + husk charcoal) with all doses of bamboo leaf silica increased the chlorophyll a, chlorophyll b and total chlorophyll. The sugar content of red beetroots was not influenced by the dose of bamboo leaf silica or the growing medium. Keywords: Chlorophyll, Husk Charcoal, Manure, Soil.